Monolithic Photonic Integrated Circuit Based on Silicon Nitride and Lithium Niobate on Insulator Hybrid Platform. Issue 10 (5th October 2022) - Jiang, Yongheng; Han, Xu; Huang, Haijin; Zhang, Pu; Dubey, Aditya; Xiao, Huifu; Yuan, Mingrui; Frigg, Andreas; Nguyen, Thach Giang; Boes, Andreas; Li, Yingtao; Ren, Guanghui; et al.
Abstract : Monolithic Photonic Integrated Circuits In article number 2200121, Yonghui Tian, Guanghui Ren and co‐workers experimentally demonstrate a monolithic photonic integrated circuit (PIC) for high‐speed data communication application on the thin‐film lithium niobate on insulator (LNOI) platform. The proposed PIC shows high data modulation rate of 70 Gbps for single channel and the total data throughput reaches up to 280 Gbps, which opens up new avenues for achieving large‐scale monolithic integration on the LNOI platform in future.